EMOTIONAL ASPECTS OF MULTIPLE SCLEROSIS - F. Godoy, Juan (Anales de Psicología / Annals of Psychology)
The main aim of this research was the assessment of emotional alterations subsequent or associated to Multiple Sclerosis. Results indicated statistically significant differences between-groups in the measure of social self-efficacy and clinically relevants in depression, anxiety-trait and total selfefficacy.